Role of cytoplasm-specific introgression in the evolution of the polyploid wheats - Gill, Bikram S. (1987)
Studies of N-banded mitotic and meiotic karyotypes of Triticum turgidum L. (2n = 28; AABB) and Triticum timopheevii Zhuk. (2n = 28; AAGG) and hybrids between them, along with observations of meiotic pairing between telocentrics of the AB-genome chromosomes and their respective homologues and homeologues in T. timopheevii, showed that chromosome 4 (m4) of Triticum monococcum L. is present (as 4A(t)) in T. timopheevii but is lacking in T. turgidum. Neither 4A nor 4B pairs with 4A(t), but 4A pairs with 4G and, for this reason and because of its banding pattern, must be considered a B-genome chromosome. T. timopheevii chromosomes 4A(t) and 3A(t) are involved in a reciprocal translocation, and 2A(t), 1G, 2G, and 5G are also involved in translocations. Chromosome arm 4BL occasionally pairs with 7G. The satellites are on the short arms of chromosomes 6A(t) and 6G of T. timopheevii and 1B and 6B of T. turgidum. It is suggested that (i) T. timopheevii orginated as an allotetraploid of Aegilops speltoides Tausch/T. monococcum and (ii) T. turgidum was derived from T. timopheevii by introgressive hybridization with an unknown diploid species, which contributed its distinctive cytoplasm, chromosome 4B or a substantial portion of it, and additional chromosome segments. Rapid fixation of 4B in T. turgidum was ensured by cytoplasm-specific transmission.